Sengketa Perdagangan Dan Hukum Lingkungan: Dampak Kebijakan Energi Hijau Terhadap Negara Berkembang (Studi Kasus Gugatan UNI Eropa Di WTO Akibat Larangan Ekspor Biji Nikel Oleh Indonesia) - Karlos Dominggo Hutagalung; Kezia Kurnia; Madani Agung Geganesywara (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
This paper explores the trade dispute between Indonesia and the European Union at the WTO, triggered by Indonesia’s decision to ban raw nickel ore exports. The policy forms part of a broader national downstreaming strategy aimed at strengthening domestic industrialization and supporting the global shift towards green energy. However, the European Union considers the measure a trade barrier that breaches liberalization principles under GATT 1994. Using a normative legal approach, this study examines relevant international trade and environmental laws, as well as Indonesia’s domestic regulations. The analysis reveals a persistent tension between developing countries’ sovereign rights to manage their natural resources and the global pressure to comply with free trade norms. The dispute highlights the need for international trade law to evolve and better accommodate the sustainable development priorities of developing economies.